THK DALAM EKOSISTEM BUDAYA LONTAR PADA MASYARAKAT DI KABUPATEN KARANGASEM - I Wayan Deddy Sumantra; Widiantana, I Kadek (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
The art of writing on palm leaves is a Balinese traditional heritage that is still alive today, although it is not found in all areas of Bali. Karangasem Regency, Bali is one of the districts with a palmyra cultural ecosystem that is still alive amidst the onslaught of globalization. The author will link the palm oil cultural ecosystem in Karangasem which still exists with the concept of Tri Hita Karana teachings using qualitative descriptive methods with data collection through observation and literature study. The research results show that the lontar cultural ecosystem in Karangasem is an application of the Tri Hita Karana (THK) teaching concept. How balance is closely intertwined between humans and God (Parahyangan), between each other (Pawongan), and with nature (Pabelasan). The theo-anthropological aspect is a Balinese human view of the cosmic by placing religious values as the "spirit" of every Balinese cultural product, including the lontar culture in Bali. The same thing can be seen in the teachings of theo-ecology as an implicit teaching in the lontar tradition in Bali. All of this goes hand in hand and is in line with the Tri Hita Karana concept.